KONTRIBUSI SUPERVISI AKADEMIK KEPALA SEKOLAH DAN SUPERVISI PENGAWAS SEKOLAH TERHADAP PROFESIONALITAS GURU - Yakop, Syarif; Syukri, M.; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstrak : Penelitian ini bertujuan untuk mengetahui seberapa besar kontribusi supervisi akademik kepala sekolah, pengawas sekolah, terhadap profesionalitas guru dalam mengelola proses pembelajaran di SMP Negeri kecamatan Sungai Raya Kabupaten Kubu Raya.Penelitian ini juga menggunakan pendekatan Kuantitatif dengan rancangan non eksperimen. Subyek penelitian ini adalah semua guru SMP Negeri di Kecamatan Sungai Raya Kabupaten Kubu Raya yang berjumlah sebanyak 64 orang guru PNS yang mempunyai masa kerja diatas 5 Tahun. Hasil penelitian ini menunjukkan bahwa Supervisi Pengawas Sekolah terhadap Profesionalitas Guru, Supervisi Akademik Kepala Sekolah yang mempuyai kontribusi yang signifikan dengan Profesionalitas Guru sebesar 00,50%. Hasil Uji F, pada penelitian ini F < F ( 9,031< 3,145 ) Ho ditolak. Kata Kunci : Kontribusi Supervisi Akademik, Profesionalisme Guru Abstract : This study aims to determine how large the contribution of academic supervision of the school principal, school superintendent, to the professionalism of teachers in managing the learning process in SMP subdistrict Sungai Raya Kubu Raya. This study also uses a quantitative approach with a non-experimental design. The subjects of this study were all teachers Junior High School in Sungai Raya Kubu Raya, amounting to as much as 64 civil servant teachers who have tenure of more than 5 years. The results of this study indicate that supervision is not correlated with the School Supervisor Teacher Professionalism, just Supervision Academic Principal significant association with Teacher Professionalism of 00.50%. F test results, in this study the F <F (9.031 <3.145) Ho is rejected. The following recommendations: 1) The Principal needs to further intensify the activities of the Academic Supervision to teachers in a systematic and programmed. 2) supervision activities in schools that had been entrusted to the supervisor should be submitted to those who truly qualify in their fields, both in terms of education as well as a comprehensive understanding of the function of strategic supervision activities. 3) Along with the development and the demands of an increasingly global world, more and more teachers should push yourself to continue to develop professionalism, both from academic and educational aspects and the quality of teaching skills. Keywords: Contributions Supervision Academic, Professional Teacher